Insomnia in the Italian Population During Covid-19 Outbreak: A Snapshot on One Major Risk Factor for Depression and Anxiety - Bacaro, Valeria; Chiabudini, Marco; Buonanno, Carlo; De Bartolo, Paola; Riemann, Dieter; Mancini, Francesco; Baglioni, Chiara (Frontiers in Psychiatry, 2020)
Objectives: One of the largest clusters of Covid-19 infections was observed in Italy. The population was forced to home confinement, exposing individuals to increased risk for insomnia, which is, in turn, associated with depression and anxiety. Through a cross-sectional online survey targeting all Italian adult population (≥ 18 yrs.), insomnia prevalence and its interactions with relevant factors were investigated. Methods: The survey was distributed from 1st April to 4th May 2020. We collected information on insomnia severity, depression, anxiety, sleep hygiene behaviours, dysfunctional beliefs about sleep, circadian preference, emotion regulation, cognitive flexibility, perceived stress, health habits, self-report of mental disorders, and variables related to individual difference in life changes due to the pandemic’s outbreak. Results: The final sample comprised 1989 persons (38.4 ± 12.8 yrs.). Prevalence of clinical insomnia was 18.6%. Results from multivariable linear regression showed that insomnia severity was associated with poor sleep hygiene behaviours (β=0.11, 95% CI [0.07-0.14]); dysfunctional beliefs about sleep (β=0.09, 95% CI [0.08-0.11]); self-reported mental disorder (β=2.51, 95% CI [1.8-3.1]); anxiety (β=0.33, 95% CI [0.25- 0.42]) and depression (β=0.24, 95% CI [0.16-0.32]) symptoms. Conclusion: An alarming high prevalence of clinical insomnia was observed. Results suggest that clinical attention should be devoted to problems of insomnia in the Italian population with respect to both prevention and treatment.